Dialyzer Reuse in the Modern Era - Prapunwatana, Piyapun; Tiranathanagul, Khajohn (Journal of the Nephrology Society of Thailand, 2023)
The use of reprocessed dialyzers has been practiced for over 5 decades. In resource-poor countries, dialyzer reuse can help save up to 30% of the cost resulting in more patients gaining access to hemodialysis. Previous studies have confirmed the safety of dialyzer reprocessing if performed under the recommended standard. Patient survival is also comparable with the use of single-use dialyzer. Today modern dialyzers are less costly and provide better biocompatibility and clearance of uremic toxins with less chemical contamination. These factors have made single-use dialyzers increasingly popular. Moreover, the current methods used to determine the efficiency of dialyzer reprocessing are based on studies published 30 years ago which focused only on the clearance of small molecules. Modern hemodialysis and dialyzers are able to provide better clearance of the middle molecules which is associated with better outcomes. The number of studies on the reprocessing of super high flux and middle cut-off dialyzers are also limited. Therefore, there is an urgent need for studies on the reprocessing and reuse of modern dialyzers, especially in the resource-poor countries in order to provide the most effective and economical hemodialysis to the patients.